Revisiting the labor market competition hypothesis in a comparative perspective: Does retirement affect opinion about immigration?. (July 2018) - Jeannet, Anne-Marie
Labor market competition is a leading explanation for defensive attitudes towards immigration but empirical support for this hypothesis is widely debated. This paper re-evaluates its explanatory power by investigating the relationship between labor market retirement and attitudes towards immigration in 14 European countries. The empirical results, based on an instrumental variable strategy to deal with potential endogeneity, find that although retirement is an important change in a person's labor market participation, it does not generally shift opinions. As a plausible explanation for this, I use a cross-national survey experiment to demonstrate that individuals who are retired retain socio-tropic orientations towards immigration, which, I argue, likely override their ego-tropic orientations. The combined evidence indicates that the labor market competition hypothesis may not be suitable as a comprehensive explanation for public opinion about immigration.